Preparation of a mesoporous silica-based nano-vehicle for dual DOX/CPT pH-triggered delivery - Maria C. Llinàs; Gabriel Martínez-Edo; Anna Cascante; Irene Porcar; Salvador Borrós; David Sánchez-García (Taylor & Francis Group, 2018)
A dual doxorubicin/camptothecin (DOX/CPT) pH-triggered drug delivery mesoporous silica nanoparticle (MSN)-based nano-vehicle has been prepared. In this drug-delivery system (DDS), CPT is loaded inside the pores of the MSNs, while DOX is covalently attached to the surface of an aldehyde-functionalized MSN through a dihydrazide-polyethylene glycol chain. Thus, DOX and the linker act as pH-sensitive gatekeeper. The system is versatile and easy to assemble, not requiring the chemical modification of the drugs. While at physiological conditions the release of the drugs is negligible, at acidic pH a burst release of DOX and a gradual release of CPT take place. In vitro cytotoxicity tests have demonstrated that this DDS can deliver efficiently DOX and CPT for combination therapy.